(untitled) (Althea Medical Journal, 2022)
Background: Tuberculous meningitis (TBM) is a severe form of extrapulmonary tuberculosis. One of the most common complications of TBM is hydrocephalus, with a higher risk of mortality. This study aimed to evaluate the outcome among TBM patients with or without hydrocephalus. Methods: This study was a retrospective cross-sectional comparative analytical study. A total sampling was employed based on the number of traceable resumes of TBM patients treated at the Department of Neurology Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2018. Results: Of the 127 data of TBM patients, 55 (43.3%) had hydrocephalus, and 72 (56.7%) did not. The median age of TBM patients with and without hydrocephalus was 34 years (IQR 26–45) and 35 years (IQR 24–44), respectively. Decreased consciousness dominated the clinical symptoms for 94.5% in the hydrocephalus group and 84.7% in the non-hydrocephalus group. Hospital-acquired pneumonia occurred mainly in the hydrocephalus group (29.1%), whereas urinary tract infections mainly occurred in without hydrocephalus group (18%). There was a significant difference between the outcome of hydrocephalus and non-hydrocephalus (p=0.005). Mortality was higher in patients with hydrocephalus compared to those without hydrocephalus. Conclusions: The outcome of TBM patients with hydrocephalus is worse than those without hydrocephalus, as reflected by a higher grade of TBM, higher mortality rate, and lower good recovery upon treatment administration. Therefore, prompt diagnosis and treatment are needed to improve the outcome and survival among TBM patients with hydrocephalus.